2007
DOI: 10.1210/jc.2006-2216
|View full text |Cite
|
Sign up to set email alerts
|

Annual Zoledronate Increases Bone Density in Highly Active Antiretroviral Therapy-Treated Human Immunodeficiency Virus-Infected Men: A Randomized Controlled Trial

Abstract: Annual administration of zoledronate is a potent and effective therapy for the prevention or treatment of bone loss in HIV-infected men. The current data provide the first trial evidence of the BMD effects of annual zoledronate beyond 1 yr in any population, as well as being the first reported trial in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 17 publications
1
74
1
Order By: Relevance
“…53,54 Intravenous zoledronic acid has also been investigated as a potential treatment option. In a randomized controlled trial conducted in 43 HIV-infected men with a BMD T-score o À 0.5, increases in lumbar spine and total hip BMD in the treatment and control groups were 8.9% versus 2.6% and 3.8% versus 0.8% after two annual infusions of zoledronic acid, 4 mg. 55 In a 4-year extension of this study, persistence of the effects on BMD and biochemical markers of bone turnover was demonstrated for at least 5 years after the second dose. 56 Significant effects on spine and hip BMD were also reported by Huang et al 57 after a single dose of zoledronic acid, 5 mg, in 30 men with osteopenia or osteoporosis.…”
Section: Pharmacological Interventionsmentioning
confidence: 61%
“…53,54 Intravenous zoledronic acid has also been investigated as a potential treatment option. In a randomized controlled trial conducted in 43 HIV-infected men with a BMD T-score o À 0.5, increases in lumbar spine and total hip BMD in the treatment and control groups were 8.9% versus 2.6% and 3.8% versus 0.8% after two annual infusions of zoledronic acid, 4 mg. 55 In a 4-year extension of this study, persistence of the effects on BMD and biochemical markers of bone turnover was demonstrated for at least 5 years after the second dose. 56 Significant effects on spine and hip BMD were also reported by Huang et al 57 after a single dose of zoledronic acid, 5 mg, in 30 men with osteopenia or osteoporosis.…”
Section: Pharmacological Interventionsmentioning
confidence: 61%
“…(Rosen et al, 2003a, Rosen et al, 2003b The efficacy and safety of zoledronic acid given concomitantly with HAART for the osteoporosis that is associated with long-term HAART administration have been evaluated in a clinical trial and found to be advantageous. (Bolland et al, 2008, Bolland et al, 2007, Huang et al, 2009) When SREs occur, they are associated with decreased activities of daily living and shorter survival. (Tsuya et al, 2007) …”
Section: Supportive Carementioning
confidence: 99%
“…Small numbers of men have also received annual infusion(s) of 4 or 5 mg of ZOL in RCTs after stroke [35] or in those receiving antiviral therapy for HIV infection [36], showing benefit in preventing bone loss or increasing bone mass in both situations.…”
Section: Use Of Zoledronic Acid In Other Causes Of Secondary Osteopormentioning
confidence: 99%